2019
DOI: 10.1109/tnsre.2019.2891090
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic Seizure Suppression by Focal Brain Cooling With Recirculating Coolant Cooling System: Modeling and Simulation

Abstract: A focal brain cooling system for treatment of refractory epilepsy that is implantable and wearable may permit patients with this condition to lead normal daily lives. We have developed such a system for cooling of the epileptic focus by delivery of cold saline to a cooling device that is implanted cranially. The outflow is pumped for circulation and cooled by a Peltier device. Here, we describe the design of the system and evaluate its feasibility by simulation. Mathematical models were constructed based on eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Thus, up to 2 mm below the brain surface should be cooled [13]. Ensuring that up to 2 mm from the surface of the brain is cooled is an essential point of treatment; however, we confirmed that the temperature 2 mm below the brain surface reaches the target temperature when the brain surface becomes the target temperature [14]. Thus, in this study, we focus not on the temperature 2 mm below the brain surface, but on the brain surface temperature.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…Thus, up to 2 mm below the brain surface should be cooled [13]. Ensuring that up to 2 mm from the surface of the brain is cooled is an essential point of treatment; however, we confirmed that the temperature 2 mm below the brain surface reaches the target temperature when the brain surface becomes the target temperature [14]. Thus, in this study, we focus not on the temperature 2 mm below the brain surface, but on the brain surface temperature.…”
Section: Introductionmentioning
confidence: 69%
“…The brain surface region just below the cooling device was 20 × 20 mm, which was divided into (50 × 50)-point grids for temperature measurement. Since we have confirmed that it takes less than 600 s to cool the brain to the target temperature, the simulation was run from the start of cooling (0 s) to 900 s, which we considered to be sufficient time for the brain surface temperature to reach the steady-state [14]. The sampling rate was 2 s. The total number of meshes in the FE simulation was about 400,000, which is within a range we have confirmed not to affect simulation results.…”
Section: A Data Collection By Means Of Fe Simulationmentioning
confidence: 99%
See 3 more Smart Citations